Burden of vision loss in the Eastern Mediterranean region, 1990-2015: findings from the Global Burden of Disease 2015 study - Safi, Sare; Jonas, Jost B.; Mokdad, Ali (International journal of public health, 2018)
OBJECTIVES: To report the estimated trend in prevalence and years lived with disability (YLDs) due to vision loss (VL) in the Eastern Mediterranean region (EMR) from 1990 to 2015. - METHODS: The estimated trends in age-standardized prevalence and the YLDs rate due to VL in 22 EMR countries were extracted from the Global Burden of Disease (GBD) 2015 study. The association of Socio-demographic Index (SDI) with changes in prevalence and YLDs of VL was evaluated using a multilevel mixed model. - RESULTS: The age-standardized prevalence of VL in the EMR was 18.2% in 1990 and 15.5% in 2015. The total age-standardized YLDs rate attributed to all-cause VL in EMR was 536.9 per 100,000 population in 1990 and 482.3 per 100,000 population in 2015. For each 0.1 unit increase in SDI, the age-standardized prevalence and YLDs rate of VL showed a reduction of 1.5% (p < 0.001) and 23.9 per 100,000 population (p < 0.001), respectively. - CONCLUSIONS: The burden of VL is high in the EMR; however, it shows a descending trend over the past 25 years. EMR countries need to establish comprehensive eye care programs in their health care systems.
Published online: 3 August 2017
Gesehen am 14.05.2020
GBD 2015 Eastern Mediterranean Region Adolescent Health Collaborators: S. Safi, J.B. Jonas, A.H. Mokdad [und 108 weitere]